La matemática escolar como lenguaje. Nuevas perspectivas de investigación y enseñanza - Rojano, Teresa (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1994)
In this article we have made a collection of the focuses and trends in the research on school mathematics considered as a language, which has characterized the research in the 80s and the beginning of the 90s —in contrast with the 70s decade, when the construction of concepts was thought of as the central objective of studying. We also deal —as a matter inherent to research— with the topic of the possible didactic implications that such focus can entail.